Epistemological dimension of design culture within Kjetil Fallan historical studies - Y. O. Butsykina (Ukrainian Cultural Studies, 2018)
Article discusses basic epistemological questions related to historical studies of design provided by the well-known design historian Kjetil Fallan. It is devoted to the analyses of the researcher’s investigation of ‘isms’ notion as a categorizing concept that can be described within cultural modes (first of all, Modern, modernity and modernism). This leads to another dimension of the "design culture" notion that provides dialectic relation between ideology and practice, constructed with ‘isms’. The latter are presented as dynamic discourses, reflected in the ‘episteme’ concept by Michel Foucault. Article analyzes Thomas Kuhn’s and Paul Feyerabend’s notion of paradigms as a structuring device in the history of science used by Fallan to contemplate the dynamics of changes in the history of design. The main idea of the theory is to outline a differential paradigmatic system in design history. That has to provide deeper investigation of design history terminology and its conceptualization principles reflection.